2020
DOI: 10.2147/clep.s264349
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Practice Status of Sentinel Lymph Node Biopsy for Early-Stage Breast Cancer Patients in China: A Multicenter Study</p>

Abstract: Background: Sentinel lymph node biopsy (SLNB) was introduced over 30 years ago, but the application of SLNB in China is unclear. This study aimed to explore the real-world implementation of SLNB among early-stage breast cancer patients in China. Methods: A multi-center, retrospective study was conducted among primary breast cancer patients from 37 hospitals in China in 2018. Their clinical data were collected and analyzed, including the implementation status of SLNB in China, subsequent processing of sentinel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…In the wake of restricting itself in the lymphatic organization, a glimmer counter is used to decide SLN which acknowledges the central waste from the tumor through a lymphatic circulation (vessel). The blue staining will help with confinement after entry point and nodes that are blue, radioactive, or both are perceived as SLN, subsequently taken out and inspected ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the wake of restricting itself in the lymphatic organization, a glimmer counter is used to decide SLN which acknowledges the central waste from the tumor through a lymphatic circulation (vessel). The blue staining will help with confinement after entry point and nodes that are blue, radioactive, or both are perceived as SLN, subsequently taken out and inspected ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eighty percent of women who underwent axillary dissection experienced complications like a decrease of mobility, seroma, paresthesia or lymphedema, ipsilateral pain where these complications are difficult to manage and may affect the quality of life significantly ( 4 ). Brar et al reported that 60% of patients complained about one or more complications, therefore a newer and non-invasive method has been used such as sentinel lymph node biopsy (SLNB) that has lower morbidity and mortality rate compare to ALND ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The SLNB technique and classification of molecular subtype were performed as described in our previous study (18). The CSBrS issued a unified data collection form to 37 medical centers in China and defined the classification criteria in the collection form.…”
Section: Sln Evaluationmentioning
confidence: 99%
“…It remains controversial whether IDC or ILC has a higher risk of non-SLNs involvement, and there is little information regarding the implementation of SLNB in patients with ILC. In our previous study, we described implementation status of SLNB and subsequent processing of positive SLNs among breast cancer patients in China (18). To explore the aforementioned issues, this nationwide cross-sectional study compared the involvement of SLNs and non-SLNs between patients with IDC and ILC.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] In 2020, the Chinese Society of Breast Surgeons of the Chinese Medical Association conducted a 37-hospital retrospective analysis and found that methylene blue dye (MBD) was used as the only tracer in more than 70% of SLNBs in breast cancer patients in China. [ 4 ] To investigate the clinical SLN identification rate (IR) using MBD and to calculate the false-negative rate (FNR) in frozen sections, we retrospectively analyzed the clinicopathological data of patients with early breast cancer who underwent SLNB with MBD at the Peking University First Hospital between January 2013 and December 2018.…”
Section: Introductionmentioning
confidence: 99%